Engaging evil: a moral anthropology - Olsen, William C.; Csordas, Thomas J. (Methodology and history in anthropology, 2019)
Intro -- Engaging Evil -- Copyright -- Contents -- List of Figures -- Acknowledgments -- Introduction -- Part I. Evil and Anthropology -- Chapter 1. From Theodicy to Homodicy -- Chapter 2. On the Concept of "Evil" in Anthropological Analyses of Political Violence -- Part II. Evil and Suffering -- Chapter 3. Speak No Evil -- Chapter 4. Mother Evil in Hell Valley -- Chapter 5. Satan on the Old Kent Road -- Chapter 6. The Transformation of Evil in Nepal -- Chapter 7. Radical Evil and the Notion of Conscience -- Chapter 8. Are Spirits Satanic? -- Part III. Evil and Violence -- Chapter 9. Engaging Evil and Excess in Palestine/Israel -- Chapter 10. The Violence of Evil -- Chapter 11. The Intention of Evil -- Chapter 12. Monsters, Sadists, and the Unspectacular Torture Experience -- Afterword -- Authors and Institutions -- Index.